Modeling of GPM and LPM in Centrifugal Pump for Obtaining Hydraulic Flow Pattern Types - Irianto, Djoni (Engineering And Technology Journal, 2024)
The types of hydraulic flow patterns in laboratory testing through the use of physical modeling tools often encounter several challenges when confronted with the use of empirical model scales, namely, the issue of scale. Water structures in the horizontal dimension do not experience highly complex issues because there are many measuring instruments available, whether self-made, home industry-produced, or industrial-grade. The presence of water volume in storage can only be tested at a clear scale, especially when it is already within a water tower (reservoir) installation with a specific height. Determining the need for water storage in a water tower is not an easy task to calculate due to differences in height, diameter, and storage capacity. Hydraulic experts often overlook these differences, which can become a problem when there is a demand for the volume of water during peak flow conditions. The solution to this issue needs to be verified by conducting model tests using a device known as the Centrifugal Pump, which has not been previously explored for laboratory research. GPM LPM model tests on this device make use of instruments and numerous pressure measuring tools supplied with pressurized water by a pump at specific, measurable volumes. To analyze the flow rate, flow coefficients, flow velocity, Reynolds number, Froude number, and test results with various speeds (speed meter), researchers test and measure the capacity of GPM LPM for each valve opening, starting with openings of 0.5, 0.75, 1.00, reading the instruments, shifting the speed from 1, 2, 3, 4, up to the highest speed, which is 12. A graph is created to display the test results of the GPM LPM speed booster device, which contains an electric motor. The test is conducted with three repetitions for each valve opening, and the speed and travel time values from the instruments on the test device are recorded and mapped. Subsequently, the analysis results of the GPM LPM test are recommended to provide information to construction planners of water structures. These results show that, under specific conditions of different speeds and valve openings, there are variations in the volume and travel time values. This information can be applied to determine the required storage capacity for each water tower building with a hydraulic flow pattern based on Reynolds number (Re) and Froude number (Fr).